2016
DOI: 10.1007/s00216-016-9625-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hydrophilic molecularly imprinted polymers via bulk polymerization combined with hydrolysis of ester groups for selective recognition of iridoid glycosides

Abstract: Hydrophilic molecularly imprinted polymers (H-MIP) with molecular recognition ability for iridoid glycosides (IGs) have been obtained via bulk polymerization combined with hydrolysis of ester groups. H-MIP were characterized by Fourier transform infrared spectroscopy (FT-IR). The hydrophilcity was measured by the contact angle measurement and the water dispersion stability. The obtained H-MIP demonstrated high selectivity and specific binding ability to five IGs in aqueous media. The group extraction efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Two MISPE methods for the determination of IGs have been developed previously . The same SPE protocol was used here to evaluate the absorbance, and the results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two MISPE methods for the determination of IGs have been developed previously . The same SPE protocol was used here to evaluate the absorbance, and the results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that 10 mg of MIPs could selectively bind 0.73 mg of GDS, compared with 0.18 mg loading for NIPs. The a The values were calculated using the reported method [26]. b The amount of IGs was obtained using the MISPE-prep-HPLC method in this work.…”
Section: Static Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] Magnetic molecularly imprinted polymers (MMIPs) that combine molecular imprinting techniques with magnetic separation techniques not only have the imprinting selectivity of the target, but can also be quickly separated under the action of an external magnetic field. [29][30][31][32][33] After target compound adsorption, the magnetic sorbent can be easily isolated from matrix solutions by applying an external magnetic field, without the need for centrifugation or filtration. [34][35][36][37] A MMIP was synthesized by suspension polymerization for selective recognition of dibenzothiophene in gasoline samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, COPs tend to lack specific molecular bonding ability. To address this issue, molecularly imprinted polymers (MIPs) have been widely studied, mainly due to its ability of selective recognition for the target molecule and their structural analogues . Novel molecularly imprinted covalent organic polymers (MICOPs) that combine the outstanding properties of both COPs and MIPs are therefore expected to be the popular adsorption media for trace analysis of FWAs in food.…”
Section: Introductionmentioning
confidence: 99%